Foreign Investment in French Polynesia - Decision of 9 April 1996 of the French Constitutional Council - Sage, Yves-Louis (Victoria University of Wellington Law Review, 1997)
Investment projects especially in tourism are booming in French Polynesia and the future prosperity of the Territory relies largely on their success. However, foreign investments remain highly controlled by the territorial authorities. The measures adopted by the Territorial Assembly on 21 November 1996 despite, or as a consequence of, decision 96-373 of the French Constitutional Council, set out all the legal requirements for foreign investors in a way which leads to strong reservations as to their validity and their practical implementation.